Efficacy and safety of riociguat replacing PDE-5is for patients with pulmonary arterial hypertension: A systematic review and meta-analysis - Liu, Yu-Yang; Qu, Yi-Yang; Wang, Shang; Luo, Ci-Jun; Qiu, Hong-Ling; Li, Hui-Ting; Yuan, Ping; Wang, Lan; Li, Jin-Ling; Jiang, Rong; Zhang, Rui (Frontiers in Pharmacology, 2023)
Introduction: Pulmonary arterial hypertension (PAH) is a rare and progressive disease. Some patients treated with phosphodiesterase type 5 inhibitors (PDE-5is) fail to reach treatment goals. As a novel soluble guanylate cyclase agonist, riociguat acts on the same pathway as PDE-5is but functions via different mechanisms. Whether riociguat is more effective and safer than PDE-5is is ambiguous. We aimed to evaluate the efficacy and safety of switching from PDE-5is to riociguat among these patients. Methods: Original published articles were retrieved from PubMed/Medline, Embase, Web of Science, Open Grey and Google Scholar. Studies that assessed the World Health Organization functional class (WHO-FC), 6-min walking distance (6MWD), pulmonary vascular resistance (PVR), mean pulmonary arterial pressure (mPAP), cardiac index (CI) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were collected. Adverse events after switching were evaluated. Results: Ten published studies were included. Compared to PDE-5is, riociguat significantly increased the 6MWD by 26.45 m weighted mean difference (WMD) = 26.45 m, 95% confidence intervals (CIs): 9.70–43.2 m, p = 0.002) and improved mPAP (WMD = −3.53, 95% CIs: −5.62–1.44 mmHg, p = 0.0009), PVR (WMD = −130.24 dyn·s·cm−5, 95% CI −187.43–73.05, p < 0.0001), CIs (WMD = 0.36 L/min·cm−2, 95% CIs: 0.25–0.47, p < 0.00001) and WHO-FC (OR = 0.11, 95% CIs: 0.08–0.16, p < 0.0001) but not NT-proBNP. In addition, we did not observe the most common side effects during the replacement of riociguat for PDE-5is. Conclusions: Compared to PDE5i, PAH patients benefit more from riociguat in hemodynamics, 6MWD, WHO-FC and biomarkers.